Qualitative α-defensin test (Synovasure) for the diagnosis of periprosthetic infection in revision total joint arthroplasty. Issue 1 (January 2017) - Sigmund, I. K.; Holinka, J.; Gamper, J.; Staats, K.; Böhler, C.; Kubista, B.; Windhager, R.
Abstract : Aims: The diagnosis of periprosthetic joint infection (PJI) remains demanding due to limitations of all the available diagnostic tests. The synovial fluid marker, α-defensin, is a promising adjunct for the assessment of potential PJI. The purpose of this study was to investigate the qualitative assessment of α-defensin, using Synovasure to detect or exclude periprosthetic infection in total joint arthroplasty. Patients and Methods: We studied 50 patients (28 women, 22 men, mean age 65 years; 20 to 89) with a clinical indication for revision arthroplasty who met the inclusion criteria of this prospective diagnostic study. The presence of α-defensin was determined using the qualitative Synovasure test and compared with standard diagnostic methods for PJI. Based on modified Musculoskeletal Infection Society (MSIS) criteria, 13 cases were categorised as septic and 36 as aseptic revisions. One test was inconclusive. Results: The Synovasure test achieved a sensitivity of 69% and a specificity of 94%. The positive and negative likelihood ratios were 12.46 and 0.33, respectively. A good diagnostic accuracy for PJI, with an area under the curve of 0.82, was demonstrated. Adjusted p-values using the method of Hochberg showed that Synovasure is as good at diagnosing PJI as histology (p = 0.0042) and bacteriology with one positive culture (p = 0.0327). Conclusion: With its ease of use and rapid results after approximately ten minutes, Synovasure may be a useful adjunct in the diagnosis of PJI. Cite this article: Bone Joint J 2017;99-B:66–72.